Optimization of Permanent Magnet Flux Switching Motor Using Sequential Technique - R. Santhiran, Yahkeish; Sulaiman, Erwan (Evolution in Electrical and Electronic Engineering, 2025)
This study focuses on the optimization of a Permanent Magnet Flux Switching Machine (PMFSM) through a sequential parameter adjustment technique aimed at maximizing torque output. PMFSMs with uneven slot-to-pole ratios typically face the drawback of reduced torque, limiting their suitability for high-performance applications. In this work, an initial baseline design was developed with fixed parameters for the stator, rotor, permanent magnets, and armature coils. The optimization process employed a sequential technique, in which these parameters were systematically modified in six distinct sequences, each involving different adjustment orders of the three core components: stator, rotor, and permanent magnets. For each sequence, the resulting machine performance was evaluated, with particular emphasis on average output torque. Comparative analysis revealed that one sequence yielded a substantial improvement in torque, effectively doubling the value compared to the initial design. The results demonstrate that sequential technique provides a practical and effective approach for enhancing the performance of PMFSMs, offering valuable insights for future design and development of high-efficiency electric machines.